2017
DOI: 10.1155/2017/1284804
|View full text |Cite
|
Sign up to set email alerts
|

Probucol Protects Rats from Cardiac Dysfunction Induced by Oxidative Stress following Cardiopulmonary Resuscitation

Abstract: Objective To investigate the protective effect of probucol on induced cardiac arrest (CA) rats and possible mechanisms. Methods Sprague Dawley rats were orally administrated with probucol at different dosage or vehicle for 5 days and subjected to a CA model by electrical stimulation, followed by cardiopulmonary resuscitation (CPR). The return of spontaneous circulation (ROSC) rate, antioxidant enzyme activities, and lipid oxidation markers were measured in serum and myocardium. Hemodynamic parameters and myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Probucol has been used as anti-atherosclerotic for many years for its affection on anti-inflammatory and anti-oxidative. According to these pharmacological activities, probucol has been used in the treatment of DMED [9,10]. Our previous study found that probucol can improve erectile function in diabetic rats, which may be related to activation of Nrf2 pathway [11].…”
Section: Introductionmentioning
confidence: 99%
“…Probucol has been used as anti-atherosclerotic for many years for its affection on anti-inflammatory and anti-oxidative. According to these pharmacological activities, probucol has been used in the treatment of DMED [9,10]. Our previous study found that probucol can improve erectile function in diabetic rats, which may be related to activation of Nrf2 pathway [11].…”
Section: Introductionmentioning
confidence: 99%
“…Probucol is a lipid-lowering drug which increases the fraction rate of LDL catabolism and has been used to treat hyperlipidemia [24]. e antioxidant and anti-inflammatory properties of probucol have been investigated using in vitro cell cultures and in vivo animal models [13,14]. It inhibits extracellular ROS and effectively reduces vascular endothelial cell apoptosis caused by oxidative stress damage [25].…”
Section: Discussionmentioning
confidence: 99%
“…Probucol is a bisphenol compound that functions as a lipid-lowering drug with anti-inflammatory and antioxidant properties and is widely used to lower cholesterol and reduce atherosclerosis in the clinic [11,12]. ere are certain reports in the literature which indicate that probucol acts as a potent oxygen radical scavenger and thus can effectively prevent oxidative stress-induced tissue damage [13,14]. Duan et al [15] and Yang et al [16] found that probucol can improve the occurrence and development of diabetic nephropathy through antioxidation and protect against diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, Probucol has been used as anti-atherosclerotic for many years for its affection on antiinflammatory and anti-oxidative. According to these pharmacological mechanisms, Probucol has been used in treatment of DMED [9,10].Our previous study found that probucol can improve erectile function in diabetic rats, which may be related to activation of Nrf2 pathway. [11] Many studies show that Nrf2 plays a protective role in many pathological processes, including DMED [11,12].…”
Section: Introductionmentioning
confidence: 99%